Symptoms of Fraud and the Role of Internal Control in Fraud Detection in the Environment of Foundation X - Leily Nur Indah Fitriana; Ria Rachmawati; Ismi Fitri Aulia (Institut Agama Islam Al-Fatimah Bojonegoro, 2024)
This study aims to analyze the symptoms of fraud and the role of internal control in detecting fraud within the environment of Foundation X. A qualitative approach was used in this research, with Vocational High School X, under Foundation X, as the study object. Informants in this study include individuals within the organization. The study results reveal potential symptoms of fraud in the environment of Foundation X, particularly a lack of internal control by the foundation’s chairman regarding the use of facilities, infrastructure, and fund accountability. Additional symptoms include accounting anomalies, such as poorly planned budgets and delayed fund disbursements, which could lead to fictitious transactions. Furthermore, an excessive lifestyle among certain superiors is an emerging indicator of fraud, as it can influence fund management in ways that increase the risk of fraudulent activities. While internal control mechanisms do play a role in fraud detection within Foundation X, their implementation is still weak. This underscores the need for regular fraud risk assessments to help eliminate fraud more effectively